2009
DOI: 10.1093/eurheartj/ehn553
|View full text |Cite
|
Sign up to set email alerts
|

Late stent malapposition risk is higher after drug-eluting stent compared with bare-metal stent implantation and associates with late stent thrombosis

Abstract: In our meta-analysis, the risk of LASM is strongly increased after DES implantation compared with BMS. Furthermore, LSM seems to be associated with late and very late ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(170 citation statements)
references
References 45 publications
8
149
1
12
Order By: Relevance
“…Several studies have reported LSM was common after DES than after bare metal stent implantation (2). Currently, the various postulated mechanisms of LSM have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported LSM was common after DES than after bare metal stent implantation (2). Currently, the various postulated mechanisms of LSM have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, lors d'un infarctus du myocarde, la présence de thrombus et la survenue d'une vasoconstriction sont des phénomènes transitoires qui peuvent exposer à l'existence d'une mal-apposition tardive une fois que le thrombus a été résorbé et que l'artère a récupéré son calibre originel. Ce phénomène de mal-apposition est considéré comme un facteur de thrombose de stent [7] ( Figure 4C). …”
Section: Limites Des Stents De Première Générationunclassified
“…Overall, a recent meta-analysis of 7 randomized trials reported that the risk of late-acquired ISA in patients with DES was 4 times higher compared to those with BMS (odds ratio 4.36, 95%CI 1.74-10.94, P= 0.002). 53 In contrast to baseline ISA as a mechanical problem, lateacquired ISA primarily results from structural vessel wall changes that occur during the follow-up period (so-called biological ISA). The most commonly reported mechanisms are (1) dissolution of thrombus present at baseline, and (2) regional positive vessel remodeling disproportional to peristent plaque area change.…”
Section: Incomplete Stent Apposition (Isa)mentioning
confidence: 99%
“…53 However, careful interpretation is still required, considering the inherent limitations of literature-based analysis of heterogeneous studies.…”
Section: Incomplete Stent Apposition (Isa)mentioning
confidence: 99%
See 1 more Smart Citation